Buone regressioni. Meità e impersonalità alla luce della nuova fenomenologia - Griffero, Tonino (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
Through an atmospherological approach, primarily inspired by the so-called New Phenomenology (Hermann Schmitz) which construes atmospheres as transmodal and sinaesthetic affordances that permeate the lived space, namely as «ecological» and affective invitations or meanings that are ontologically rooted in things and near-things, the paper defines personal identity with what is perceived, i.e. not with an inner and closed pysche sphere but with what outer and impersonal affects actually produce on the perceiver.